Estudo da qualidade de polpas e sementes do jenipapo (Genipa americana L.) para elaboração de barras de cereais - Costa, Jennifer Anne Martins da (2011)
Genipap possesses sweet and acidic pulp, with several seeds coated with mucilage endocarp. The Genipap is a very perishable fruit with high respiration rate. When harvested, it mature quickly and runs the risk of higher post-harvest losses. This study was aimed to verify the physical and chemical quality of fresh pulp, osmotically dehydrated (OD) pulp and of genipap flour (SF) obtained from fruits of two maturity stages. The maturity stages studied were of half-ripe and ripe fruits. For osmotic dehydration of genipap pulp, syrup 50 °Brix was used and drying was performed at 60°C. Prior to the osmotic dehydration of genipap pulp, four treatments were performed, with the first application being without metabisulfite, sodium alginate and calcium chloride; the second with the use of metabisulphite and without alginate and calcium chloride; the third without the use of metabisulphite and application of alginate and calcium chloride; and the fourth with the application of metabisulphite and alginate and calcium chloride. The seeds were submitted to pre-drying at 60 °C for 4 hours, crushed in a mill and again dried at 60 °C for 2 hours. In the optimization of the product manufacture of cereal bars a 23 factorial planning with three central points was used and data analyzed by Response Surface Methodology. The independent variables were substitutions of SF and OD in the total of flakes and brown sugar, respectively. While the response variable was the acceptance of cereal bars by consumers which took into consideration the attributes of appearance, flavor, texture, overall impression and purchase intent. Among the various pre-treatments of osmotic dehydration, the best average was found in the treatment without application of metabisulfite, sodium alginate and calcium chloride, and it was also the most attractive. In microscopic analysis changes occurred in the appearance of dehydrated cubes. The results showed that the mature genipaps were considered ideal for the preparation cereal bars, since it retained the best physical-chemical characteristics with respect to genipaps in dehydrated form and flour quality. The cereal bar optimized was composed by replacement the standard formulation of 20% of SF in the total cereals and 20% of OD in the brown sugar. The averages of the attributes studied ranged from the terms of the hedonic scale "I liked slightly" to "I really liked." The SF was the ingredient that resulted in negative effect on the results of the dependent variable, however the interaction of this with OD, attenuated this impact. The brownish homogeneous color, higher density, lower compression force and shear force characterized the cereal bar as optimized cereal bar when compared with standard cereal bar. It was also possible to verify that substitution by SF and by OD enriched the cereal bar for the ash, lipids, carbohydrates contents and energy, and especially of total protein and total fiber content, with an increase of 19.5% and 39.8%, respectively. Thus, the use of osmotically dehydrated pulp and genipap flour seed not only are feasible in the fruit processing and utilization of waste, but also in the production of cereal bars with excellent physical-chemical composition and acceptance by consumers.